Prenatal Growth in Uterus of Does by Superovulation - ADRIANI ADRIANI; ADI SUDONO; TOHA SUTARDI; ASMEN MANALU; I KETUT SUTAMA (Bogor Agricultural University, Indonesia, 2007)
Thirty six Etawah-grade does (BW 20.4-44.2 kg, age 2.5-7 years) were used to study the efficacy of increasing secretion of endogenous hormones of pregnancy by superovulation of does to stimulate of growth prenatal in uterus. The does were injected with pregnant mare serum gonadotrophin (PMSG), 0 IU/kg BW [grouped into nonsuperovulation-NSO] and 15 IU/kg BW [grouped into Superovulation-SO]. Intravaginal sponge (60 mg medroxyprogesterone acetate) was applied for 14 days to synchronize estrus cycle. Twenty four hours prior to sponge removal, PMSG was injected to stimulate superovulation. After sponge removal, five experimental does were mixed with one buck for natural mating. Superovulation prior to mating increased number of corpora lutea, mean of maternal serum estradiol concentration, progesterone concentration, litter size, average birth weight and average milk yield, by 112, 67, 42, 27, 32, and 35%, respectively. Those were correlated with the increase of uterine, corpora lutea, and individual birth weight. Key words: Etawah-grade, hormone, kids, superovulation